On-site measurement of indoor environment quality in a Chinese healthcare facility with a semi-closed hospital street. (15th April 2020) - Tang, Haida; Ding, Jianhua; Lin, Zhenghao
Abstract: With hospitals in megacities becoming larger, the hospital-street layout has an increasingly larger impact on the efficiency and stability of a hospital. In this study, the indoor-environment quality of a semi-closed hospital street and the adjacent outpatient waiting areas were investigated using objective on-site measurements and subjective questionnaire-based surveys. The results revealed that the hospital street had an over-heated and over-humid environment, with a humidity ratio of 17.7–18.6 g/kg. Consequently, the occupant-dissatisfaction rate in terms of the thermal environment exceeded 50%. The blending of air from the hospital street with that from the outpatient waiting areas led to an indoor air temperature of 27–29 °C in the latter, which exceeds the standard threshold of 26 °C. The indoor air quality (in terms of CO2, total volatile organic compounds (TVOC), and PM2.5 concentration) of the hospital street was good, ensuring compliance with existing Chinese standards. However, spot glare through the transparent ethylene-tetra-fluoro-ethylene (ETFE) membrane roof and uneven illumination in the hospital street caused visual discomfort. Vibration of the ETFE membrane roof during rainfall led to noise levels of 79.5 dB(A) in the hospital street and 70 dB(A) in the outpatient waiting rooms, severely reducing acoustic comfort and resulting in an occupant-dissatisfaction rate of 60%. Thus, this study provides data, both objective and subjective, of the indoor-environment quality in both hospital streets and outpatient waiting areas. Highlights: Indoor environment quality in a semi-closed hospital street was on-site measured. Objective measurement and subjective surveys were conducted simultaneously. The hospital street and adjacent outpatient rooms were overheated and humid. The roof vibration in rain caused a noise level of 79.5 dB(A) in the hospital street.